Case Report: Low-Level Maternal Mosaicism of a Novel CREBBP Variant Causes Recurrent Rubinstein-Taybi Syndrome in Two Siblings of a Chinese Family - Lin, Shaobin; He, Zhiming; Huang, Linhuan; Liu, Jialiu; Lei, Ting; Wu, Jianzhu; Huang, Peizhi; Zhou, Yi; Luo, Yanmin (Frontiers in Genetics, 2021)
Familial Rubinstein-Taybi syndrome (RSTS) with recurrent RSTS siblings and apparently unaffected parents is rare; such cases might result from parental somatic and/or germline mosaicism. Parental low-level (<10%) germline mosaicism in the CREBBP-associated RSTS family has not been reported. Here, we present our studies of a Chinese family with two RSTS siblings and apparently unaffected parents. We detected the apparent de novo variant (DNV) c.3235C>T (p.Gln1079*) in CREBBP in the siblings via trio whole-exome sequencing. High-depth next-generation sequencing (NGS) for the parents revealed a low-level (<10%) mosaic variant in both the peripheral blood (3.64%) and buccal mucosa (1.94%) of the unaffected mother, indicating maternal somatic and germline mosaicism. Peripheral blood RNA-sequencing analysis for the offspring and parents indicated that the c.3235C>T (p.Gln1079*) nonsense variant did not trigger nonsense-mediated mRNA decay to reduce CREBBP mRNA levels. Transcriptome analysis revealed 151 downregulated mRNAs and 132 upregulated mRNAs between the patients and normal individuals. This study emphasizes that high-depth NGS using multiple specimens might be applied for a family with an affected sibling caused by an apparent CREBBP DNV to identify potential low-level parental mosaicism and provide an assessment of recurrence risk.